Implementasi Wireless Mesh Network berbasis Protokol Routing BATMAN untuk Video Live Streaming dengan menggunakan Fitur Network Coding - Muhammad Fattah Na'im Pang Ripto; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Live Streaming Video is one technology that is still used today. The main challenge with streaming is that it requires a large bandwidth to run properly. With a modern multi-hop network topology and intersecting node paths, the requirement for connection to live streaming video is getting bigger due to busy network traffic. This has an impact on the value of Quality of Services (QoS) and user convenience. Network coding can be used at relay nodes to increase the QoS value, especially throughput on the network by channeling packets from two sources simultaneously. The research was carried out using the BATMAN proactive routing protocol, which only looks for the best next-hop path so that it is efficient in a Wireless Mesh Network with a total of five hardware nodes. Quality of Services (QoS) testing is carried out on two devices, namely node C and node D which stream on node A and node B with node E as an intermediary. After the network coding was implemented, the throughput value in the test at node C increased at QCIF resolution of 0.00014 MB/s and CIF of 0.109199 MB/s compared to normal conditions without network coding. While at node D, the increase in throughput after network coding also occurs at QCIF resolution of 0.000336 MB/s and CIF of 0.000345 MB/s. The results of the test parameters are in accordance with the theory of using network coding, which after implementing the throughput value shows an increase.